2019
DOI: 10.1002/ghg.1851
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of CO2 capture performance using piperazine (PZ) and diethylenetriamine (DETA) bi‐solvent blends

Abstract: The carbon dioxide post‐combustion capture process using amine solutions is considered the most appropriate method for CO2 capture from flue gas in power plants. This paper focuses on the CO2 capture performance of six common organic amines. Two amines, piperazine (PZ) and diethylenetriamine (DETA), which showed better performance, were then filtered out to form amine blends to improve performance further. The absorption heat from the CO2 absorbing process was measured directly using an advanced C80 micro calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The CO 2 absorption heat for each solution was measured directly with a high-precision microcalorimeter, a powerful tool that is being increasingly used and approved for this type of determination. , The experimental setup and procedure followed were the same as those already described by Zheng and Liu in previous papers. , Briefly, before the absorption process starts, an appropriate amount of the tested blend solution was placed in the sample cell and the reaction temperature was set to the desired value of 313 K. When both the sample temperature and the heat flow signal were stabilized, a gaseous mixture with a known amount of CO 2 (in these experiments, 15% v/v) was continuously injected into the reactor. The chemical absorption of CO 2 by the sorbent involves variations in the heat flow, continuously recorded by the microcalorimeter.…”
Section: Methodsmentioning
confidence: 99%
“…The CO 2 absorption heat for each solution was measured directly with a high-precision microcalorimeter, a powerful tool that is being increasingly used and approved for this type of determination. , The experimental setup and procedure followed were the same as those already described by Zheng and Liu in previous papers. , Briefly, before the absorption process starts, an appropriate amount of the tested blend solution was placed in the sample cell and the reaction temperature was set to the desired value of 313 K. When both the sample temperature and the heat flow signal were stabilized, a gaseous mixture with a known amount of CO 2 (in these experiments, 15% v/v) was continuously injected into the reactor. The chemical absorption of CO 2 by the sorbent involves variations in the heat flow, continuously recorded by the microcalorimeter.…”
Section: Methodsmentioning
confidence: 99%
“…The energy penalty during the CO 2 regeneration process (Q regen , GJ ton −1 CO 2 ) usually consists of the heat of absorption (Q des ), the sensible heat (Q sen ), and the latent heat of vaporization (Q laten ), which can be expressed below (Liu et al 2019b):…”
Section: Thermodynamic Datamentioning
confidence: 99%
“…A blended solution of 20% DETA (diethelenetriamine) and 10% PZ showed an increase of 42% compared to 30% MEA. This blended solution also decreased the regeneration energy, making the solution cost-friendly …”
Section: Introductionmentioning
confidence: 99%
“…This blended solution also decreased the regeneration energy, making the solution costfriendly. 51 AMP (amino methyl propanol) and MDEA (methyldiethanolamine) have low energy consumption for solvent regeneration, but they have a low absorption rate. 52,53 Compared to 30% of MEA with (23 wt % AMP + 7 wt % PZ), it was reported that overall mass transfer coefficient K y a v increases from 10 to 28 kmol/m 3 h when the operation pressure is 0.1−4.0 MPa for the blended AMP + PZ, whereas for 30% MEA, at same operating pressure, the K y a v increases from 8 to 23 kmol/m 3 h. 54 This proves that, due to the higher mass transfer, the blended AMP + PZ is more effective at improving the CO 2 absorption reaction rate than is MEA.…”
mentioning
confidence: 99%